Burkina Faso : Selected Issues. (IMF Staff Country Reports; Country Report, 2008)
This paper assesses the link between public investment and economic growth in Burkina Faso. It also evaluates Burkina Faso's external competitiveness by using a comparison of REER to its equilibrium levels and a survey-based assessment of overall competitiveness. The report attempts to quantify the impact of rainfall and terms-of-trade shocks on the Burkinabe economy and draws policy measures to lessen external shocks. The report assesses that industrial mining has become a source of foreign exchange and government revenue, which requires transparent management and accountability.